Evaluation of stripe rust resistance and analysis of resistance genes in wheat genotypes from Pakistan and Southwest China - Abbas, Sakina; Li, Yunfang; Lu, Jing; Hu, Jianming; Zhang, Xinnuo; Lv, Xue; Shahzad, Armghan; Ao, Donghui; Abbas, Maryam; Wu, Yu; Zhang, Lei; Fayyaz, Muhammad (Frontiers in Plant Science, 2024)
Introduction Stripe rust, caused by Puccinia striiformis f. sp. tritici, poses a significant threat to wheat quality and production worldwide. The rapid evolution of Pst races caused several resistance genes to be ineffective. Methods This study evaluated stripe rust resistance genes in 349 Pakistan and Southwest China genotypes. We utilized previously published functional and linked molecular markers to detect 13 major stripe rust resistance genes: Yr5, Yr9, Yr10, Yr15, Yr17, Yr18, Yr26, Yr29, Yr30, Yr36, Yr48, Yr65, and YrSp. Field evaluations assessed IT and resistance levels, while the impact of gene combinations on resistance was also analyzed. Results Field evaluations showed that over 60% of Chuanyu wheat, 50% of recent Pakistani cultivars, and 20% of historic Pakistani lines were resistant to current stripe rust races. In Chuanyu wheat, the dominant genes were Yr17, YrSp, and Yr48; however, Yr17, Yr26, and YrSp were overused, while Yr36 was absent, and Yr18 was rare. In historic lines, Yr5, Yr17, Yr18, and Yr26 were prevalent, with Yr15, Yr26, and YrSp demonstrating effective resistance against current stripe rust races. Furthermore, the study identified specific combinations of Yr genes (Yr26+Yr48, Yr29+Yr5, Yr26+Yr30, and Yr30+Yr17) that enhanced resistance to Pst. Discussion This research highlights effective resistance genes and gene combinations for stripe rust in wheat and emphasizes the deployment of durable resistance. The findings guide the strategic use of these genes in breeding programs aimed at developing durable resistance in wheat genotypes in Pakistan and Southwest China.